2022
DOI: 10.1136/jitc-2022-005249
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tumor microenvironment and biomarkers of immune checkpoint inhibitor response in metastatic renal cell carcinoma

Abstract: BackgroundImmunotherapy combinations including ipilimumab and nivolumab are now the standard of care for untreated metastatic renal cell carcinoma (mRCC). Biomarkers of response are lacking to predict patients who will have a favorable or unfavorable response to immunotherapy. This study aimed to use the OmniSeq transcriptome-based platform to develop biomarkers of response to immunotherapy.MethodsTwo cohorts of patients were retrospectively collected. These included an investigational cohort of patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“… 48 This correlation aligns with findings by Brown et al, who identified distinct expression patterns of immune markers differentiating responders from non-responders to ICIs. 49 These patterns are potentially predictive of treatment outcomes, suggesting that a nuanced understanding of tumor-infiltrating lymphocytes (TILs) could substantially refine the personalization of immunotherapy in RCC. Further emphasizing the complexity of the immune landscape in ccRCC, the comprehensive analyses by de Vries-Brilland et al highlighted how the density and type of immune infiltrates might dictate therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“… 48 This correlation aligns with findings by Brown et al, who identified distinct expression patterns of immune markers differentiating responders from non-responders to ICIs. 49 These patterns are potentially predictive of treatment outcomes, suggesting that a nuanced understanding of tumor-infiltrating lymphocytes (TILs) could substantially refine the personalization of immunotherapy in RCC. Further emphasizing the complexity of the immune landscape in ccRCC, the comprehensive analyses by de Vries-Brilland et al highlighted how the density and type of immune infiltrates might dictate therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The human CC chemokine receptors such as CCR4 and CCR7 involve in T cell trafficking [ 39 ]. Over expressed CCR4 appeared to be treated as a biomarker for immune checkpoint inhibitor therapeutic response in renal cancer patients [ 40 ]. Similar to our findings, a high-level of CCR4 was also correlated with good prognosis in HNSC suffers through joining in immune infiltration [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other checkpoint inhibitors, such as antibodies targeting T cell immunoglobulin (VISTA), mucin domain 3 (TIM-3), lymphocyte activation gene 3 (LAG-3), and TIGIT, are also being evaluated in clinical trials for the treatment of ccRCC [63].…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%